Mechanical properties of double-solid waste cement stabilized Macadam - Rui Tao; Xuejiao Cheng; Yong Jin; Jiangang Qiao; Xue Zhang; Daehyeon Kim; Jinjie Liu (Scientific Reports)
Abstract Cement stabilized macadam base has high strength and excellent bearing capacity, but the problems of water-temperature sensitivity, easy shrinkage cracking and large demand for aggregate limit the further development and application of cement stabilized macadam base. At the same time, with the economy development, the increase of solid waste, such as waste tires and construction waste, has caused great pressure on the ecological environment. In order to ensure better mechanical properties and shrinkage resistance of the cement stabilized macadam on the basis of full use of solid waste. In this paper, mechanical properties tests such as unconfined compressive strength, splitting strength, compressive resilient modulus and shrinkage properties tests such as dry shrinkage and temperature shrinkage were conducted. Double-solid waste cement stabilized macadam mixture were prepared by partially replace fine and coarse aggregates with waste crumb rubber of different mesh and replacement ratios and recycled concrete aggregate of different replacement ratios, and their properties were investigated. The experimental results show that: (1) The good elasticity and toughness of waste crumb rubber can improve the crack resistance of cement stabilized macadam mixture. While the mechanical properties such as unconfined compressive strength and splitting strength will be reduced. (2) The mechanical properties of double-solid waste cement stabilized macadam mixture can be improved by partially replacing coarse aggregate with appropriate amount of recycled concrete aggregate with porous and rough surface, but it will adversely affect its shrinkage resistance. (3) The recommended particle size and replacement ratio of waste crumb rubber in double-solid waste cement stabilized macadam mixture are 40 mesh and 0.5%, respectively, and the recommended replacement ratio of recycled concrete aggregate is 75%. The mechanical properties indexes of double-solid waste cement stabilized macadam mixture can meet the specification requirements.